A multi‐strategy fuzzy control method based on the Takagi‐Sugeno model. (2nd August 2022) - Al‐Hadithi, Basil Mohammed; Adánez, José Miguel; Jiménez, Agustín
Abstract: In this work, a new multi‐strategy fuzzy control (MSFC) based on fuzzy fusion techniques for the control of multivariable nonlinear systems is proposed. This new nonlinear control method is a mixture of different control techniques by fuzzy interpolation using the fuzzy Takagi‐Sugeno model. It combines various control strategies to achieve smooth transient responses and zero steady state error. The following techniques are merged within the proposed MSFC structure: an optimal state feedback control that yields an optimal transient response, optimal control through an incremental state model that returns a zero steady state error, and a constant input control to maintain the system behavior within predefined boundaries whenever the MSFC method is applied.